Experimental study on premixed flame combustion of annular burner with CO2 dilution based on OH-PLIF technology - Zhonghua Wang (Taylor & Francis Group, 2019)
In view of the combustion characteristics of annular chamber of micro gas turbine, a planar laser-induced fluorescence (PLIF) technique was used to investigate the methane/air premixed turbulent multiple flames in the annular combustor and the effect of CO2 on the characteristic parameters of flame structure was further discussed. The results show that the distribution of the OH radicals exhibits a ring structure with flame lift and bifurcation phenomena. The instantaneous and average image of OH-PLIF reveals that the multiple flames have the common characteristics of turbulent and laminar premixed flame structure. The quantitative analysis of the characteristic parameters of flame structure shows that the increase of CO2 concentration, the flame premixed conical structure is stretched, the overall flame chemistry reaction area is reduced and the intensity of local combustion is weakened; The Coanda effect causes the flame to bend towards the inner wall, and the relative bending of the outer flame increases as well as the flame angle.